2011
DOI: 10.1590/s0102-36162011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Radiografias em inclinação lateral como fator preditivo da correção cirúrgica na escoliose idiopática do adolescente

Abstract: Objective: To evaluate the use of x-rays in dorsal decubitus, as a predictive factor for surgical correction of the main thoracic curve using pedicle screws, on patients with idiopathic adolescent scoliosis. Method: Twenty patients with idiopathic adolescent scoliosis of Lenke types 1A and 1B who were operated using a technique only involving pedicle screws by means of the posterior route were evaluated clinically and radiographically. The difference between the expected and actual postoperative results was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…We believe that this may be a reflection of the surgical correction, since the spinal rotations caused by the scoliosis form the ribs, turning them back and forth on the convex side, and forward on the concave side [14,15]. It is possible that these changes directly reflect a better alignment of the sternum and the ribs after the surgical correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this may be a reflection of the surgical correction, since the spinal rotations caused by the scoliosis form the ribs, turning them back and forth on the convex side, and forward on the concave side [14,15]. It is possible that these changes directly reflect a better alignment of the sternum and the ribs after the surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…We considered as the initial information the clinically significant minimum difference between the PRE and PO1 periods of 20° and the difference between the PRE and LPO periods of 30° [14]. When a power of more than 0.90 was defined as a significance level of 0.05, the minimum sample size was 11 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographs of the entire spine were produced on panoramic film (90 cm × 30 cm), in anteroposterior view (AP), lateral view (P) and active supine lateral oblique anteroposterior view. 7 The following parameters were evaluated as possible predictive factors for trunk compensation: Cobb angles of the proximal thoracic curve (TPX), TPR and TL/L 4 ; Risser sign 8 ; distal level of the arthrodesis; and translation of the lumbar apical vertebra. 9 The percentage correction of the curves was calculated in accordance with the formula proposed by Suk et al 6 : …”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9] Flexibility can be analyzed by several methods: bending in the standing or dorsal horizontal decubitus positions, fulcrum bending, traction, traction under general anesthesia, among others. [5][6][7][10][11][12] Currently, bending radiographs are considered the gold standard for flexibility assessment, because they are easy to perform and are one of the parameters included in the classifications. 5,7,13,14 It is known that in curves greater than 60 degrees traction is better than the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,13,14 It is known that in curves greater than 60 degrees traction is better than the other methods. 7,12 More recently, flexibility has begun to be assessed using the traction under anesthesia method. Some studies have demonstrated equivalence with the bending positions, with better correction due to muscle relaxation.…”
Section: Introductionmentioning
confidence: 99%